1994
DOI: 10.1016/0378-1097(94)90110-4
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of 4-chlorophenol by Azotobacter sp. GP1: Structure of the meta cleavage product of 4-chlorocatechol

Abstract: A mutant strain of Azotobacter sp. GP1 converted 4-chlorophenol to 4-chlorocatechol under cometabolic conditions. Under the same conditions the wild-type strain accumulated a yellow compound, which by chemical and spectroscopic methods was identified as 5-chloro-2-hydroxy-6-oxohexadienoic acid (5-chloro-2-hydroxy-muconic semialdehyde). The structure of this compound indicates a meta-proximal cleavage of 4-chlorocatechol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
21
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 13 publications
2
21
0
Order By: Relevance
“…strain GP1, to induce the TCP-dehalogenating enzyme suggests that this organism degrades phenol and TCP via different pathways. This agrees with findings obtained by induction experiments with whole cells in the presence and absence of chloramphenicol (14) and with results concerning the metabolism of phenol (32).…”
Section: Discussionsupporting
confidence: 92%
“…strain GP1, to induce the TCP-dehalogenating enzyme suggests that this organism degrades phenol and TCP via different pathways. This agrees with findings obtained by induction experiments with whole cells in the presence and absence of chloramphenicol (14) and with results concerning the metabolism of phenol (32).…”
Section: Discussionsupporting
confidence: 92%
“…This highly reactive acyl chloride, if released from the enzyme, should be hydrolyzed to 2-hydroxyhexa-2,4-dienoic acid, which shows an absorption maximum at 290 nm at pH 7.5 (38). In contrast, the product of the metacleavage of 4-chlorocatechol has been identified as 5-chloro-2-hydroxy-6-oxohexadienoic acid (30,45) and shows the typical behavior of classical meta-cleavage products. The ring fission product of 3-chlorocatechol after a distal extradiol cleavage would be the isomeric compound 3-chloro-2-hydroxy-6-oxohexadienoic acid exhibiting the same chromophor.…”
Section: Discussionmentioning
confidence: 99%
“…© 1998 The Society for Applied Microbiology chlorinated phenols (Steiert and Crawford 1986 ;Li et al 1991 ;Kiyohara et al 1992 ;Wieser et al 1994 ;Fava et al 1995 ;Tomasi et al 1995 ;Bock et al 1996 ;Koh et al 1997). Under anaerobic conditions, CPs, independently from the substitution grade, are often reductively dechlorinated up to phenol in fresh water sediments and by microbial consortia under sulphate-reducing and methanogenic conditions (Zhang and Wiegel 1990 ;Häggblom and Young 1990 ;Turner Togna et al 1995) ; few pure cultures have been shown to degrade CPs anaerobically (Mohn and Kennedy 1992 ;Utkin et al 1995 ;Christiansen and Ahring 1996).…”
Section: Introductionmentioning
confidence: 99%